Nuciferine ameliorates hepatic steatosis in high‐fat diet/streptozocin‐induced diabetic mice through a PPARα/PPARγ coactivator‐1α pathway. (11th October 2018) - Zhang, Chao; Deng, Jianjun; Liu, Dan; Tuo, Xingxia; Xiao, Lei; Lai, Baochang; Yao, Qinyu; Liu, Jia; Yang, Haixia; Wang, Nanping
Abstract : Background and Purpose: Nuciferine, an alkaloid found in Nelumbo nucifera leaves, alleviates dyslipidemia in vivo . However, whether it improves liver injury in diabetic conditions and the underlying mechanism is unclear. The present study aimed to investigate the effects of nuciferine on lipid and glucose metabolism in a murine model of Type 2 diabetes mellitus (T2DM) and to determine the underlying mechanisms of these effects. Experimental Approach: A murine model of T2DM was induced by high‐fat diet (HFD) feeding combined with streptozocin (STZ) injections, and the diabetic mice were treated with nuciferine in their food. The underlying mechanism of the anti‐steatotic effect of nuciferine was further explored in HepG2 hepatocytes cultured with palmitic acid. Major signalling profiles involved in fatty acid oxidation were then evaluated, using Western blot, RT‐qPCR and si‐RNA techniques, along with immunohistochemistry. Key Results: Nuciferine restored impaired glucose tolerance and insulin resistance in diabetic mice. Hepatic levels of total cholesterol, triglycerides and LDL were decreased, as were the number of lipid droplets, by nuciferine treatment. Furthermore, nuciferine up‐regulated β‐oxidation related genes in livers of diabetic mice. Luciferase reporter cell assay showed that nuciferine directly reversed palmitic acid‐induced inhibition of PPARα transcriptional activity. Silencing PPARγ coactivator‐1α (PGC1α) expression in HepG2 cells abolished the effects of nuciferine in accelerating β‐oxidation. Conclusions and Implications: Nuciferine improved lipid profile and attenuated hepatic steatosis in HFD/STZ‐induced diabetic mice by activating the PPARα/PGC1α pathway. Nuciferine may be a potentially important candidate in improving hepatic steatosis and the management of T2DM.